2020
DOI: 10.1097/nmd.0000000000001224
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of High Psychosocial Functioning in Bipolar Disorder

Abstract: The aim of this study was to identify predictors of high psychosocial functioning in patients with bipolar disorder (BD). One hundred forty-five outpatients with BD and 50 healthy controls were included. Patients were categorized as having high psychosocial functioning if they concomitantly met three conditions: a) General Assessment of Functioning greater than 90, b) full-time employment, and c) full functional recovery. Clinical, demographical, and neurocognitive variables were assessed and considered as pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Therefore, a relative big sample and large age span sample of patients with bipolar disorder are needed in further studies. Results from Pearson partial correlation showed that executive function, working and visual memory did moderately correlated with functional domains which is consistent with one previous research ( 14 ). However, there still exists controversies about which neurocognitive domains could explain the heterogeneity of functional outcomes ( 57 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, a relative big sample and large age span sample of patients with bipolar disorder are needed in further studies. Results from Pearson partial correlation showed that executive function, working and visual memory did moderately correlated with functional domains which is consistent with one previous research ( 14 ). However, there still exists controversies about which neurocognitive domains could explain the heterogeneity of functional outcomes ( 57 ).…”
Section: Discussionsupporting
confidence: 91%
“…Burdick et al provided empirical evidence on significant heterogeneity of neurocognition in patients with BD, and three different neurocognitive subgroups were found, meanwhile, the demographic and clinical characteristics were different among these subgroups ( 12 ), which was consistent with the other study ( 13 ). And evidence suggests that heterogeneity of psychosocial functioning in BD might exist, which was based on the same or even better neurocognitive performance as the general population ( 4 , 14 ). In addition, Sole et al first confirmed that in euthymic patients with BD also existed three different functional subgroups based on the Functioning Assessment Short Test ( FAST ) domain scores, and three groups have been reported as low functioning group (LF), intermediate functioning group (MF) and good functioning group (GF) ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational functioning was defined in 23 of the 82 included papers (Wingo et al 2010;Gilbert and Marwaha 2013;Martinez-Aran et al 2007;Depp et al 2012b;Tse et al 2014;Lomastro et al 2020;Altshuler et al 2007;Bello 2009;Bonnin et al 2014;Bowie et al 2010;Deckersbach et al 2010;Drakopoulos et al 2020;Duarte et al 2016;Harvey et al 2010;Levy et al 2013;Luo et al 2020;Mur et al 2008;Sanchez-Moreno et al 2009;Solé et al 2018;Strassnig et al 2017;Tabarés-Seisdedos et al 2008;Torrent et al 2007;Wilder-Willis 2001). We have categorized the definitions regarding the two aspects of occupational functioning mentioned in the introduction: work participation and work functioning.…”
Section: Definitions Of Occupational Functioningmentioning
confidence: 99%
“…Moreover, the presence of subsyndromal depressive symptoms represents one of the main predictors of functional impairment, in particular of attitudes such as giving up and self-blame [ 32 , 39 , 40 , 41 ]. Recent papers focused specifically on neurocognitive function [ 27 , 28 , 30 , 42 , 43 ], as cognitive deficits were considered one of the main determinants of functional impairment, and evidence showed that better performance in some areas, such as attention, executive functions, and verbal memory, are predictors of better psychosocial functioning [ 44 ].…”
Section: Introductionmentioning
confidence: 99%